Pendampingan dan Pemasaran Produk Pepaya Jepang Secara Online dalam Program Pengabdian Masyarakat KWT Melati 02 Karawaci (KKN : Upaya Peningkatan Nilai Ekonomi Lokal): Online Assistance and Marketing of Japanese Papaya Products in the KWT Melati 02 Karawaci Community Service Program (KKN: Efforts to Increase Local Economic Value) - Guntoro, Yudhi; Idris, Navual; Putra, Raja Fadillah; Syaputra, Rahman; Marwati, Annisa (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The community in Kampung Papaya Japan, Karawaci sub-district is a community that is good at managing natural products that are not in great demand and thrive in the surrounding environment in such a way as to become new products that have added value, but in the process, there are many obstacles both in terms of branding, packaging, a proper business place and especially in the field of marketing, through this community service we will assist in marketing products online so that the products produced by KWT melati 2 Karawaci women reach more consumers without incurring large costs. The method used is discussion and demonstration, training on how to manage a good and correct online store, and others. The results show that by plunging or opening online stores on several platforms can increase sales and reach new potential markets that previously could not be reached.